A novel AIE-based supramolecular polymer gel serves as an ultrasensitive detection and efficient separation material for multiple heavy metal ions. Issue 34 (15th August 2019) - Chen, Yan-Yan; Gong, Guan-Fei; Fan, Yan-Qing; Zhou, Qi; Zhang, Qin-Peng; Yao, Hong; Zhang, You-Ming; Wei, Tai-Bao; Lin, Qi
Abstract : A novel, easy to fabricate AIE-based supramolecular polymer gel material enables the ultrasensitive detection and efficient separation of multiple heavy metal ions. Abstract : Recently, ultrasensitive stimuli-responsive materials have received extensive attention due to their high sensitivity and wide applications. Herein, we report a novel approach to design ultrasensitive responsive materials by rationally introducing the aggregation-induced emission (AIE) effect into supramolecular polymer gels. According to this approach, by rationally introducing self-assembly moieties and a fluorophore, the obtained gelator DNS can act as an AIEgen; it showed strong AIE after aggregating into the supramolecular polymer gel GDNS. More interestingly, because the aggregation of DNS led to amplification of the detective signal, the AIE-based supramolecular polymer gel GDNS could ultrasensitively detect the heavy metal ions Hg 2+, Cu 2+, and Fe 3+ by a signal amplification mechanism; the lowest detection limits reached 10 −11 M. In addition, the xerogel of GDNS could adsorb and separate Hg 2+, Cu 2+, and Fe 3+ from aqueous solution with favourable adsorption properties, and the adsorption rates ranged from 94.70% to 99.37%. Furthermore, the gel GDNS could act as a convenient test kit for Hg 2+, Cu 2+, and Fe 3+ as well as a smart fluorescent display material.